Comunicação e existência em tempo real na cibercultura: a experiência do ciberespaço à luz da questão da técnica em Heidegger - Assis, André Sendra de (2011)
This research deals with the phenomenon of real-time existence and its determination starting from the glocal context (neither global nor local), seeking to grasp the possibilities of understanding this condition and its unfoldments. This work, which is of a purely theoretical nature, proposes to view this issue in light of Heidegger's reflections about the problems of technique, assuming that this conception makes it possible to think radically about the specific determination of a world in which the "real" has been transformed into the "virtual." The foundations for this research are the concepts of spectralization of Marc Guillaume, mediatic visibility of Eugênio Trivinho, technique of Martin Heidegger, and nihilism of Friedrich Nietzsche. Enabled by the propagation of network technologies and considering the sociohistorical moment that corresponds to the last phase of metaphysics and the abandonment of self, as attested by Heidegger, cyberculture is the horizon upon which the question of real-time existence is historically inscribed. Hence, cyberculture is treated as the place where existence is spectralized, where everything is determined relationally, in consonance with the Heideggerian thesis of the essence of modern technique and with the consideration of virtualization as a "natural" unfolding within a metaphysics of absence. The issue pertaining to the main research problem, i.e., real-time existence as an emblematic construct of contemporaneity, involves a discussion of what this form of existence proposes within the ambit of an understanding of the civilizing process concerning the question of technique. The theoretical and epistemological foundations of this research encompass, first and foremost, the works of Heidegger with respect to the issue of technique and of existence, and, with regard to real-time existence and the glocal and cybercultural context, the works of Trivinho, especially insofar as they refer, within this argumentation, to Paul Virilio's thinking in his approach to the concept of medi~atic light and of deterritorialization, and to that of Marc Guillaume with respect to spectralization. Other important sources of reference were Jean Baudrillard's notion of hypertely and Sfez's idea of tautism. For reasons of theoretical coherence, this work is founded on the phenomenological method of investigation. With these attributes, this research aims to understand the phenomenon of real-time existence from a differentiated standpoint that can contribute, in terms of an epistemological renewal of this concept, to the theoretical and critical development of studies on cyberculture and Communication